Certified Information Security Manager (CISM) Cert Prep (2022): 4 Incident Management. - Chapple, Mike (linkedin.com, 2022)
Study for the Incident Management domain of the CISM certification exam, which tests your ability to identify, triage, and resolve security incidents.